2022
DOI: 10.1021/acs.bioconjchem.2c00383
|View full text |Cite
|
Sign up to set email alerts
|

Niosomes as Biocompatible Scaffolds for the Multivalent Presentation of Tumor-Associated Antigens (TACAs) to the Immune System

Abstract: Fully synthetic tumor-associated carbohydrate antigen (TACA)-based vaccines are a promising strategy to treat cancer. To overcome the intrinsic low immunogenicity of TACAs, the choice of the antigens’ analogues and multivalent presentation have been proved to be successful. Here, we present the preparation, characterization, and in vitro screening of niosomes displaying multiple copies of the mucin antigen TnThr (niosomes-7) or of TnThr mimetic 1 (niosomes-2). Unprecedentedly, structural differences, likely re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…32,106 Previous studies demonstrated the niosomal ability, as a vaccine delivery vector, to intensify the immune response against the delivered antigens derived from infectious agents or tumour cells. 107,108 The efficient deliverability of inorganic material-based nanoparticles such as gold nanoparticles has also promoted their utilisation in vaccine delivery. 109 Additionally, tubular nanostructures such as carbon nanotubes previously showed significant enhancement in immune response potency as vaccine carriers.…”
Section: Future Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…32,106 Previous studies demonstrated the niosomal ability, as a vaccine delivery vector, to intensify the immune response against the delivered antigens derived from infectious agents or tumour cells. 107,108 The efficient deliverability of inorganic material-based nanoparticles such as gold nanoparticles has also promoted their utilisation in vaccine delivery. 109 Additionally, tubular nanostructures such as carbon nanotubes previously showed significant enhancement in immune response potency as vaccine carriers.…”
Section: Future Perspectivementioning
confidence: 99%
“…32,106 Previous studies demonstrated the niosomal ability, as a vaccine delivery vector, to intensify the immune response against the delivered antigens derived from infectious agents or tumour cells. 107,108 The efficient deliverability of inorganic Fig. 4 Peptide nanofiber-mediated mucosal non-invasive vaccination approach.…”
Section: Comparative Studies and Hybrid Systems For Enhanced Vaccine ...mentioning
confidence: 99%
“…In parenteral delivery, non-ionic surfactant vesicles have exhibited promising potential to act as antibacterial agents in conjunction with various antigens and peptides. 27,43 A research conducted by Fallarini, Silvia, et al 45 found that glycosylated niosomes have the potential to induce macrophage differentiation towards an M1 phenotype. This phenotype is crucial for presenting antigens to responsive T cells in a proinflammatory environment, essential for generating an effective anticancer immune response.…”
Section: Nasal Drug Deliverymentioning
confidence: 99%
“…This approach proves to be ideal for the development of synthetic tumor vaccines. 45 3.10 Diagnostic imaging: Theranostic nano-platforms have gained considerable attention due to their extensive potential in therapy and diagnostics using niosomes, stemming from their remarkable success and advancements in producing unique nanostructures. Consequently, theranostics has emerged as a prevalent method for tailored therapy.…”
Section: Nasal Drug Deliverymentioning
confidence: 99%
“…Among them, the lamellar phase has drawn much interest from the biological point of view -mimicking as a model of a cell membrane [8]. Further, this model is used in the formulation of niosome -a drug delivery agent used in pharmaceutical and medicinal elds [4,[9][10][11]. Niosomes are vesicles formed by non-ionic surfactants like glycolipid, meanwhile, lysosome are vesicles formed by phospholipids.…”
Section: Introductionmentioning
confidence: 99%